Chelation of diamine ligands to zinc porphyrin monolayers amide-linked to glass - McCallien, D; Burn, P; Anderson, H (1997)
A pentafluorophenol active-ester porphyrin has been synthesised and covalently attached to an aminopropylsilylated glass surface by amide bond formation. Zinc is inserted into the surface-bound porphyrins and their interaction with amine ligands is investigated by UV-VIS spectroscopy. The high affinity of the zinc porphyrin monolayers for bidentate ligands such as 1,4-diazabicyclo[2.2.2]octane, 4,4′-bipyrldyl and 1,3-di(4-pyridyl)propane demonstrates that the porphyrins are in close proximity on the surface and yet are not so tightly packed as to prevent ligand intercalation. Effective molarities of up to 0.35 mol dm-3 are observed.